2015
DOI: 10.1111/apce.12060
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficiency Between Cooperative, Savings and Commercial Banks in Europe Using the Frontier Approach

Abstract: We test competing hypotheses concerning the comparative behavior of shareholder‐owned commercial banks and stakeholder‐orientated cooperative and savings banks in European banking. One hypothesis is that the risk culture and business models of stakeholder and shareholder‐owned banks have become more alike and so cost efficiency has converged between bank ownership structures. The alternative hypothesis suggests that institutional differences do matter and lead, amongst other things, to variation in network eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…) and other European banks (e.g. Makinen and Jones ). When the geographic stratification of the Italian territory has been taken into account, results show that banks located in Centre–Southern regions are less cost efficient than those located in Northern regions confirming again what has already been found for the Italian banking system (e.g.…”
Section: Empirical Evidencementioning
confidence: 99%
“…) and other European banks (e.g. Makinen and Jones ). When the geographic stratification of the Italian territory has been taken into account, results show that banks located in Centre–Southern regions are less cost efficient than those located in Northern regions confirming again what has already been found for the Italian banking system (e.g.…”
Section: Empirical Evidencementioning
confidence: 99%
“…For example, for the US, Klinedinst (2012: 4) finds that, compared to commercial banks, credit unions "…are often estimated to have a better return on assets and… higher efficiency in that they control more assets per dollar spent on salaries than commercial and savings banks....". Outside the US other firm level studies that find positive effects of cooperatives compared to other organizational forms include Ferri, Kalmi and Karola (2014) and Mäkinen and Jones (2015). Also, econometric case study evidence for Finnish co-operative banks (Jones, Kalmi and Kauhanen, 2012) is consistent with the hypothesis that employee members in cooperative banks are apt to have increased loyalty and lower turnover and that, in turn, this may lead to extensive training of the workforce and more accumulation of human capital.…”
Section: Discussionmentioning
confidence: 61%
“…The main criticism generally levelled at financial cooperatives is the absence of market discipline, which is considered as a powerful governance mechanism that guards against inefficiency. However, tradable shares also create pressure to engage in short‐term risky activity (Mäkinen and Jones ). Recent studies show that the performance and efficiency of financial cooperatives tend to be at least as good as those of private commercial banks (Ayadi et al.…”
Section: Financial Cooperatives a Unique Financial Institutionmentioning
confidence: 99%
“…Cooperative banks also have better loan quality and lower asset risk. Lastly, using the largest European banks database (521 European banks from 1994 to 2010), Mäkinen and Jones () found that cooperative banks were about 3 percentage points more efficient than commercial and savings banks. The authors also find a lower variance in the inefficiency score for cooperative banks.…”
Section: Financial Cooperatives a Unique Financial Institutionmentioning
confidence: 99%